Selection of endogenous genes for gene expression studies in Eucalyptus under biotic (Puccinia psidii) and abiotic (acibenzolar-S-methyl) stresses using RT-qPCR - Boava, Leonardo P [UNESP]; Laia, Marcelo L [UNESP]; Jacob, Tiago R [UNESP]; Dabbas, Karina M [UNESP]; Gonçalves, Janaína F [UNESP]; Ferro, Jesus A [UNESP]; Ferro, Maria It [UNESP]; Furtado, Edson L [UNESP] (Springer Nature, 2010)
Background: Rust caused by Puccinia psidii Winter has been limiting for the establishment of new Eucalyptus plantations, as well as for resprouting of susceptible genetic materials. Identifying host genes involved in defense responses is important to elucidate resistance mechanisms. Reverse transcription-quantitative PCR is the most common method of mRNA quantitation for gene expression analysis. This method generally employs a reference gene as an internal control to normalize results. A good endogenous control transcript shows minimal variation due to experimental conditions. Findings. We analyzed the expression of 13 genes to identify transcripts with minimal variation in leaves of 60-day-old clonal seedlings of two Eucalyptus clones (rust-resistant and susceptible) subjected to biotic (P. psidii) and abiotic (acibenzolar-S-methyl, ASM) stresses. Conclusions. For tissue samples of clones that did not receive any stimulus, a combination of the eEF2 and EglDH genes was the best control for normalization. When pathogen-inoculated and uninoculated plant samples were compared, eEF2 and UBQ together were more appropriate as normalizers. In ASM-treated and untreated leaves of both clones, transcripts of the CYP and elF4B genes combined were the ones with minimal variation. Finally, when comparing expression in both clones for ASM-treated leaves, P. psidii-inoculated leaves, ASM-treated plus P. psidii-inoculated leaves, and their respective controls, the genes with the most stable expression were EgIDH and UBQ. The chitinase gene, which is highly expressed in studies on plant resistance to phytopathogens, was used to confirm variation in gene expression due to the treatments. © 2010 Laia et al; licensee BioMed Central Ltd.
Keywords: Eucalyptus; Puccinia psidii